Centralisation of cash management: Still advisable? - Bartsch Christian; Wim Westerman (The Central European Review of Economics and Management (CEREM), 2023)
Aim: This article builds upon recent evidence that centralisation of cash management activities, often advocated by enthusiast protagonists from the academic, corporate and consultancy world, has given way to decentralisation thereof. The aim of the article is to underpin the idea that such moves may be good. Research design: The article provides an historical overview on the centralisation starting in the 1980s, stagnating later on and reversing recently, not just for reasons of political tensions and pandemic reasons. Findings: There are structural reasons for firms being more critical on centralisation of cash management, including still lasting limits to its implementation and recent changes in the corporate and finance sectors. Originality: The present study argues that firms may rightfully decentralise the cash management, while also making clear to there are no "one fits all" solutions to the issue. Implications: Firms may want to overthink the organisation of their cash management in the light of new developments. Follow-up research in terms of case studies and surveys may help to further guide them.
Keywords: B27; G20; L23; 330; cash management; (de-) centralisation; role of banks